Rapid non-invasive prenatal screening test for trisomy 21 based on digital droplet PCR - Laššáková, Soňa; Šenkyřík, Pavel; Pazourková, Eva; Hořínek, Aleš; Calda, Pavel; Břešťák, Miroslav; Světnicová, Kamila; Neužil, Pavel; Korabečná, Marie (Scientific reports, 2023)
Non-invasive prenatal tests for the detection of fetal aneuploidies are predominantly based on the analysis of cell-free DNA (cfDNA) from the plasma of pregnant women by next-generation sequencing. The development of alternative tests for routine genetic laboratories is therefore desirable. Multiplex digital droplet PCR was used to detect 16 amplicons from chromosome 21 and 16 amplicons from chromosome 18 as the reference. Two fluorescently labeled lock nucleic acid probes were used for the detection of reaction products. The required accuracy was achieved by examining 12 chips from each patient using Stilla technology. The plasma cfDNA of 26 pregnant women with euploid pregnancies and 16 plasma samples from pregnancies with trisomy 21 were analyzed to determine the cutoff value for sample classification. The test was validated in a blind study on 30 plasma samples from pregnant patients with a risk for trisomy 21 ranging from 1:4 to 1:801. The results were in complete agreement with the results of the invasive diagnostic procedure (sensitivity, specificity, PPV, and NPV of 100%). Low cost, and speed of analysis make it a potential screening method for implementation into the clinical workflow to support the combined biochemical and ultrasound results indicating a high risk for trisomy 21.
Keywords: prenatální diagnóza; trizomie; Trisomy; Cell-Free Nucleic Acids; lidé; Female; Downův syndrom; Pregnancy; Aneuploidy; těhotenství; Down Syndrome; aneuploidie; polymerázová řetězová reakce; volné cirkulující nukleové kyseliny; Prenatal Diagnosis; Polymerase Chain Reaction; ženské pohlaví; Humans